KAJIAN MODAL SOSIAL PADA KELOMPOK TANI SUKA MAJU DAN KELOMPOK TANI TUMOU TOU DI DESA KOPIWANGKER KECAMATAN LANGOWAN BARAT KABUPATEN MINAHASA - Hansen Jeremia Wowiling; Martha Mareyke Sendow; Welson Marthen Wangke (Sam Ratulangi University, 2019)
The research was conducted from September 2018 to February 2019, starting from preparationÂ to preparing the report. The sampling method in this study was to use the Total Sampling method with aÂ number of samples taken as many as 100% of the members of two farmer groups namely Suka MajuÂ farmer groups as many as 17 respondents and Tumou Tou farmer groups as many as 17 respondents. TheÂ total number of respondents was 34 farmers. The data used are primary data and secondary data.Â Primary data was collected by interviewing all respondents with the help of a list of questions preparedÂ before. Secondary data was collected from documents owned by both farmer groups, local bookstores,Â the internet through google search engines in the form of books and â€œskripsiâ€ related to the topic of thisÂ research, namely farmers' social capital. Data analysis was carried out descriptively which wasÂ presented in table form and then interpreted. The results showed that the elements of social capitalÂ namely norms, networks, beliefs, reciprocal relationships, and values have been able to improve theÂ existence and cohesiveness of Suka Maju farmer groups because the social capital of Suka Maju farmerÂ groups is very good compared to Tumou Tou farmer groups. Viewed from all sides, the Tani Suka MajuÂ group has better social capital than the Tumou Tou farmer group. Thus to improve the existence andÂ cohesiveness of Tumou Tou farmer group like Suka Maju farmer group, it is necessary to improve thequality of social capital as owned by farmer groups Suka Maju.*eprm*